PELATIHAN PENGEMASAN DAN PELABELAN BANDENG SAPIT DI UD. BAROKAH GUNUNG ANYAR TAMBAK - Winarti, Sri; Ningsih, Yuni (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
Gunung Anyar Tambak is one of the villages that is located adjacent to the UPN "Veteran" campus in East Java. Most (2/3) of the Gunung Anyar Tambak area is the pond area, which has the main yield is milkfish. Besides being sold in fresh form, milkfish from ponds from Gunung Anyar Tambak are also processed into a variety of processed products including shredded, crackers, soft thorns and milkfish ?sapit?. Milkfish ?Sapit? is a processed milkfish which is unique in its serving. The milkfish are clamped using bamboo stems and then processed using a choice of spices that make a distinctive taste in this dish. Processing by burning, causing a distinctive aroma that is not forgotten. Barokah is one of the community groups of ?sapit? milkfish processing in RW I of Gunung Anyar Tambak Village which consists of 6 people. Chairman of UD. Barokan is Hj's. Khasibah, explained that most of the milkfish produced are only fulfilling orders from the surrounding area and orders from outside the city to be used as souvenirs typical of Surabaya. From observations and interviews it is known that the problem in processing milkfish is a very simple packaging that is a very thin plastic bag that is not closed. The second problem is that the packaging has no labeling at all, even though the label can identify the identity of the product in the package. The importance of labels on food products in addition to being the identity of the packaged product is also a communication between producers and consumers. Therefore a very absolute label must be given to the marketed food products. Training has been conducted on packaging and labeling milkfish ?sapit? in UD. BAROKAH, Gunung Anyar Tambak, Surabaya. Before being packed with a vacuum packer, milkfish saplings are first dried in a cabinet dryer for 3 hours at 60°C. Labeling on milkfish packaging is in accordance with the law on food labeling on primary (plastic) and secondary (carton) packaging. In addition to providing training, our team also donates dryers and Vacuum Sealers.